Evaluation of Mechanical and Water Absorption Properties of Alkaline-Treated Sawdust-Reinforced Polypropylene Composite - Eyasu Ferede (Journal of Engineering)
Sawdust is a natural composite obtained from natural resources such as shrubs and trees and in a large amount from the wood industry as a waste. This study aimed to evaluate the mechanical and water absorption properties of alkaline-treated wood sawdust-reinforced polypropylene composite. The composites were manufactured by the melt-mixing method followed by compression molding with amounts of wood sawdust ranging from 10, 20, 30, and 40 to 50 wt. % by volume. The produced composites were characterized for their mechanical and water absorption characteristics. The results indicated that increasing the amount of wood sawdust content up to 40% improves the tensile, flexural, impact, and compressive strength of the composites but after the wood sawdust contents reach 40%, the mechanical properties of the composite were decreased. Water absorption rate has increased with an increase in the wood sawdust proportion; this is due to the presence of –OH groups on the surface of wood particles. From the result of this study, it can be also concluded that the optimal mechanical and water absorption properties were attained at 40% wood sawdust content. Therefore, sawdust can be used as filler and reinforcement in the PP matrix, which will reduce cost and give environmental benefits.